Предмет: Алгебра,
автор: TheMaRkHDB
преобразовать в многочлен
а)
(b+3)*(b-3)+(2b+3)
б)
(c+2)*(c-3)-(c+1)*(c+3)
Ответы
Автор ответа:
0
а) (b+3)*(b-3)+(2b+3)= b²-9+2b+3=b²+2b-6
б) (c+2)*(c-3)-(c+1)*(c+3)= c²-3c+2c-6-(c²+3c+c+3)=c²-c-6-c²-4c-3=-5c-9
..................................................................................................................................................................
.///////////////////////////////////////////////////////////////////////////////////////////////////////////
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Информатика,
автор: nesteanastya19
Предмет: Английский язык,
автор: Folicassh
Предмет: Математика,
автор: Ульяна7